2013
DOI: 10.2166/wst.2013.408
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a single stage vertical flow constructed wetland system treating raw domestic sewage in Brazil

Abstract: This study investigated the behaviour of two intermittently fed vertical flow constructed wetlands (one planted with Tifton 85 and the other unplanted) working in parallel, treating raw municipal sewage in Brazil for a population equivalent around 100 inhabitants. Based on a monitoring programme of over 2 years, the following items were evaluated: influence of batch frequency and the presence of Tifton 85 on the wetlands performance in terms of several physico-chemical and biological constituents. The unit wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 0 publications
0
7
0
7
Order By: Relevance
“…Contudo, a duração do regime operacional de 7 dias de alimentação sobrecarregou o sistema, que no 6º dia apresentou dificuldades de drenagem do líquido que se acumulou na superfície, impedindo assim, o potencial de difusão de oxigênio no leito filtrante, justificando os menores valores nos últimos dias. Em um estudo realizado na mesma planta de tratamento, após 2 anos do início de sua operação, foram identificadas concentrações médias de 5,1 mg O2 L -1 no efluente para o regime de operação de 24 pulsos d -1 consecutivamente por 2,5 dias de alimentação seguido de 4,5 dias de descanso [13]. É notório que com o passar do tempo (7 anos de operação) as condições de transferência de oxigênio para o leito filtrante foram afetadas, influenciadas principalmente pelo acúmulo de sólidos na parte superior do filtro (média de 6,6 cm) e pela alimentação de uma mesma unidade feita por um período de tempo maior.…”
Section: Resultados E Discussõesunclassified
See 1 more Smart Citation
“…Contudo, a duração do regime operacional de 7 dias de alimentação sobrecarregou o sistema, que no 6º dia apresentou dificuldades de drenagem do líquido que se acumulou na superfície, impedindo assim, o potencial de difusão de oxigênio no leito filtrante, justificando os menores valores nos últimos dias. Em um estudo realizado na mesma planta de tratamento, após 2 anos do início de sua operação, foram identificadas concentrações médias de 5,1 mg O2 L -1 no efluente para o regime de operação de 24 pulsos d -1 consecutivamente por 2,5 dias de alimentação seguido de 4,5 dias de descanso [13]. É notório que com o passar do tempo (7 anos de operação) as condições de transferência de oxigênio para o leito filtrante foram afetadas, influenciadas principalmente pelo acúmulo de sólidos na parte superior do filtro (média de 6,6 cm) e pela alimentação de uma mesma unidade feita por um período de tempo maior.…”
Section: Resultados E Discussõesunclassified
“…Comparando com os resultados de Lana et al [13] que pesquisou o mesmo sistema da presente pesquisa, o desempenho foi similar com o passar do tempo em termos de N-NH4 + (60% e 58% para este estudo) ao contrário dos resultados obtidos para DQO, que apresentou decaimento na eficiência de remoção de 80% para 69%.…”
Section: Resultados E Discussõesunclassified
“…In addition, Hill and Sobsey (2001) found that the presence of plants in a horizontal subsurface flow constructed wetland improved the removal of Salmonella when compared to an unplanted unit. However, for vertical flow constructed subsurface wetlands, no significant difference in the removal efficiency was observed of thermotolerant coliforms, E. coli, somatic coliphages, and F-specific bacteriophages for planted and unplanted systems (Torrens et al, 2009;Lana et al, 2013).…”
Section: Mechanical Filtration and Media/plant Importancementioning
confidence: 91%
“…Wand et al (2007) reported an average attachment of 8×10 6 bacteria cells per gram of sand in a column study simulating a vertical flow constructed wetland. Lana et al (2013) investigated planted and unplanted vertical flow subsurface wetlands receiving a mean influent helminth egg concentration of 61 eggs/L of domestic wastewater. In that study, helminth eggs were removed similarly in the planted and non-planted system (97% and 96%, respectively).…”
Section: Mechanical Filtration and Media/plant Importancementioning
confidence: 99%
“…Subsurface flow wetlands can be subdivided into vertical and horizontal flow. In the vertical flow, the effluent to be treated is distributed in the support layer surface, being gradually drained next, and going through all the layers of the constructed bed vertically (LANA et al, 2013). On the other hand, in the horizontal flow, the effluent goes through the filling material and macrophyte roots horizontally (MATOS; VON SPERLING; MATOS, 2018).…”
mentioning
confidence: 99%